Differential expression of Toll-like receptor genes (TLR2 and TLR4) across different tissues of riverine buffalo - DUBEY, P K; GOYAL, S; NAMITA, NAMITA; MISHRA, S K; GAHLAWAT, S K; KATARIA, R S (The Indian Journal of Animal Sciences, 2016)
Toll-like receptors (TLRs) are one of the important pattern recognizing receptors which are responsible for the induction of innate as well as adaptive immune response against a wide range of microbial components. Among different TLRs, TLR2 and TLR4 are expressed on the cell surface identifying Gram-positive and Gram-negative bacterial components. The present study was undertaken to analyze the expression of TLR2 and TLR4 genes in different buffalo tissues by using highly sensitive real-time PCR technique. Although the expression of both the genes was observed in all the 8 different tissues taken for the present study, the maximum expression of TLR2 was seen in blood followed by skin, lungs and spleen and the lowest expression was found in the uterus. TLR4 showed maximum expression in blood followed by skin, lungs, mammary gland of non-lactating, lactating buffalo and heifer and the lowest expression was seen again in the uterus.The findings suggest both the genes having important functions in blood and skin, the first line of protection for pathogenic challenge apart from other organs in buffalo.